2014
DOI: 10.1093/jac/dku021
|View full text |Cite
|
Sign up to set email alerts
|

In vitro susceptibility of zoospores and hyphae of Pythium insidiosum to antifungals

Abstract: We conclude that the use of hyphal inocula of P. insidiosum for in vitro susceptibility tests could be a suitable method for evaluating antimicrobial susceptibility, particularly when it is not possible to obtain a standardized zoospore inoculum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
23
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 17 publications
1
23
0
2
Order By: Relevance
“…However, in our hands, generation of zoospores from Thai strains is difficult and labor-intensive and did not provide enough zoospores for the susceptibility testing. Likewise, hyphal suspensions, prepared as described by other investigators (15,30,31) were not reproducibly uniform in our hands (data not shown). As an alternative, we have used the method of Brown and coworkers (32), starting with agar plugs of active hyphal growth and measuring radial growth of the hyphae.…”
Section: Discussionmentioning
confidence: 41%
See 3 more Smart Citations
“…However, in our hands, generation of zoospores from Thai strains is difficult and labor-intensive and did not provide enough zoospores for the susceptibility testing. Likewise, hyphal suspensions, prepared as described by other investigators (15,30,31) were not reproducibly uniform in our hands (data not shown). As an alternative, we have used the method of Brown and coworkers (32), starting with agar plugs of active hyphal growth and measuring radial growth of the hyphae.…”
Section: Discussionmentioning
confidence: 41%
“…insidiosum, respectively. To completely inhibit the growth of 50% of the isolates tested required at least 16 mg/liter of itraconazole and 4 mg/liter of terbinafine in the studies by Argenta et al (34) and at least 64 mg/liter of itraconazole and 8 mg/liter of terbinafine in those by Fonseca et al (30), while our group found that more than 128 mg/liter of both drugs was required. The different inhibitory effects of the two drugs against Py.…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…The broth microdilution (BMD) reference assay was carried out following the CLSI M38-A2 guidelines (11), as previously described (12,13). The final concentrations of the antimicrobial agents tested in the wells ranged from 1,024 to 0.5 g/ml for mupirocin and tobramycin and from 256 to 0.125 g/ml for azithromycin, clarithromycin, clindamycin, chloramphenicol, doxycycline, erythromycin, florfenicol, fluconazole, fusidic acid, lincomycin, linezolid, minocycline, roxithromycin, terbinafine, tetracycline, tigecycline, and tilmicosin.…”
mentioning
confidence: 99%